QoS multicast routing using explore best path - Singh, Jaipal; Veeraraghavan, P.; Singh, S. (Elsevier Science, 2006)
One of the most active research areas in networking is quality of service (QoS). The most fundamental requirement for QoS is the ability to find a path that can provide the required network resources between two nodes. These nodes will use QoS routing to find a feasible QoS path between both of them. In this paper, we present a distributed multicast QoS routing architecture that uses probes to find a quick and scalable QoS path between a joining router and the multicast tree. Any router that receives this probe will only know its neighbours and it will create a link to the previous router from where the probe comes from. The joining router will join the multicast tree by following these links on each router until it reaches the tree. Analysis of this method shows that the convergence rate and message overhead is lower than other similar schemes.